Modernization Of Islamic Religious Education In The 21st Century Through The Merdeka Curriculum - Edo Alvizar Dayusman (Proceeding International Conference on Religion, Science and Education, 2023)
Industrial progress has required people to have the ability to face all the challenges that exist today. The 21st century has an impact on human life, educational institutions are expected to be resilient in facing challenges and changes that arise in the community. To anticipate the negative impact of the progress of science and technology and the rapid pace of modernization, every individual is required to be able to adapt and fortify themselves. Education is always evolving and faced with changing times and its problems. For this reason, inevitably education must be designed to follow the changing currents of the times, especially Islamic religious education. If Islamic religious education is not designed to keep up with changes, then Islamic religious education will be behind the pace of development of the times. Therefore, changes in Islamic religious education must be related to the changing times and the needs of society. Efforts to build a globally-minded Islamic religious education are not an easy matter, because at the same time Islamic religious education must have an obligation to preserve, instill the values of Islamic religious teachings and on the other hand strive to instill a locally based character. Currently, the Ministry of Education and Culture has established a new curriculum called the Independent Curriculum. This curriculum is designed to emphasize strengthening the character of the Pancasila student profile which aims to shape the character of students in accordance with the needs of the current global market. This research is a type of qualitative research using the library research method. This study aims to analyze the modernization of Islamic religious education through an independent curriculum. The result of this research is that the modernization of Islamic religious education with a global perspective can be done through an independent curriculum with a student-centered learning system by prioritizing aspects of strengthening the profile of Pancasila students so that students are able to develop their abilities without neglecting Islamic values.